Hercynine content in widely consumed commercial beverages. (December 2018) - Sotgia, Salvatore; Zinellu, Angelo; Forteschi, Mauro; Paliogiannis, Panagiotis; Pinna, Gerard A.; Mangoni, Arduino A.; Carru, Ciriaco
Abstract: Hercynine, the main biosynthetic precursor and oxidative metabolite of ergothioneine, was measured by an LC-ESI-MS/MS method in tea, coffee, beer, and wine samples. Results showed that hercynine was detectable and measurable in all beverage. Among teas, the higher concentration was in the black variety (170.45 ± 7.84 ng/mg of dry weight) followed by the white (130.63 ± 8.79 ng/mg of dry weight) and green ones (71.62 ± 6.13 and 47.43 ± 7.66 ng/mg of dry weight). Compared to teas, coffees had less amount of hercynine with more homogeneous levels that appear unlinked to the kind of mixture (100% Arabica 12.92 ± 1.01 ng/mg of dry weight, 50/50 Arabica/Robusta 10.52 ± 0.38 ng/mg of dry weight, and decaffeinated 8.59 ± 0.75 ng/mg of dry weight). Overall, the red wines had the highest values of hercynine compared to the whites (379.57 ± 238.15 vs. 575.51 ± 62.60 nmol/L). In the latter, hercynine concentrations showed a trend toward an increase with increasing pH values. Hercynine concentrations in the beers were similar to the levels in wines, and there was no difference between traditional and gluten-free sample (679.24 ± 0.92 vs. 570.58 ± 0.88 nmol/L). These data highlight the potential of hercynine as a possible marker of antioxidant activity of ergothioneine in beverages and food. Highlights: Hercynine and ergothioneine concentrations in several beverages were quantified. Ergothioneine was undetectable in tea, coffee, wine, and beer. Hercynine could act as a marker of the antioxidant activity of ergothioneine. Hercynine could act as a marker of food quality.